The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1097/gox.0000000000000825
|View full text |Cite
|
Sign up to set email alerts
|

A Proximally Based Sural Fasciocutaneous Flap for the Treatment of Recurrent Peroneal Neuropathy: A Case Report

Abstract: Summary:Surgical treatment for recurrent, common peroneal neuropathy has not been reported. Herein, we describe a successfully treated case using the proximally based sural fasciocutaneous flap after reneurolysis of the adhesive common peroneal nerve. A 33-year-old man received a neurolysis operation for entrapment neuropathy of the common peroneal nerve 2 years before first admission in our clinic. Although motor nerve conduction studies showed a marked improvement after the primary operation, the patient alw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…11 The results showed that the patient experienced a good functional recovery after the surgery. 11 Moreover, wrapping the released CPN using a sural fasciocutaneous flap may help prevent postoperative readhesion. 11 With regards to the aforementioned findings, we proposed two hypotheses to explain why CPN repairs fail based on our recent clinical experience: first, a CPN injury is typically superficial, and the nerve bed experiences a suboptimal nutritional environment, thus making it prone to entrapment and challenging to recover from.…”
Section: Introductionmentioning
confidence: 88%
See 4 more Smart Citations
“…11 The results showed that the patient experienced a good functional recovery after the surgery. 11 Moreover, wrapping the released CPN using a sural fasciocutaneous flap may help prevent postoperative readhesion. 11 With regards to the aforementioned findings, we proposed two hypotheses to explain why CPN repairs fail based on our recent clinical experience: first, a CPN injury is typically superficial, and the nerve bed experiences a suboptimal nutritional environment, thus making it prone to entrapment and challenging to recover from.…”
Section: Introductionmentioning
confidence: 88%
“…The results showed that the patient experienced a good functional recovery after the surgery 11 . Moreover, wrapping the released CPN using a sural fasciocutaneous flap may help prevent postoperative re‐adhesion 11 …”
Section: Introductionmentioning
confidence: 95%
See 3 more Smart Citations